Two-photon microscopy imaging of thy1GFP-M transgenic mice: a novel animal model to investigate brain dendritic cell subsets in vivo. - Claudia Laperchia (Public Library of Science (PLoS), 2013)
Transgenic mice expressing fluorescent proteins in specific cell populations are widely used for in vivo brain studies with two-photon fluorescence (TPF) microscopy. Mice of the thy1GFP-M line have been engineered for selective expression of green fluorescent protein (GFP) in neuronal populations. Here, we report that TPF microscopy reveals, at the brain surface of these mice, also motile non-neuronal GFP+ cells. We have analyzed the behavior of these cells in vivo and characterized in brain sections their immunophenotype.With TPF imaging, motile GFP+ cells were found in the meninges, subarachnoid space and upper cortical layers. The striking feature of these cells was their ability to move across the brain parenchyma, exhibiting evident shape changes during their scanning-like motion. In brain sections, GFP+ cells were immunonegative to antigens recognizing motile cells such as migratory neuroblasts, neuronal and glial precursors, mast cells, and fibroblasts. GFP+ non-neuronal cells exhibited instead the characteristic features and immunophenotype (CD11c and major histocompatibility complex molecule class II immunopositivity) of dendritic cells (DCs), and were immunonegative to the microglial marker Iba-1. GFP+ cells were also identified in lymph nodes and blood of thy1GFP-M mice, supporting their identity as DCs. Thus, TPF microscopy has here allowed the visualization for the first time of the motile behavior of brain DCs in situ. The results indicate that the thy1GFP-M mouse line provides a novel animal model for the study of subsets of these professional antigen-presenting cells in the brain. Information on brain DCs is still very limited and imaging in thy1GFP-M mice has a great potential for analyses of DC-neuron interaction in normal and pathological conditions.